1985
DOI: 10.1002/bjs.1800720717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rectal washout on bacterial counts in the rectal stump

Abstract: Forty-three patients undergoing a restorative colorectal resection were randomized to have their rectal stump washed out with either 0.9 per cent saline, 2.5 per cent povidone-iodine or 0.3 per cent sodium hypochlorite. The bacterial counts before and after washout for Escherichia coli and Bacteroides fragilis were compared using the Mann-Whitney U test. There was no significant difference in the counts for E. coli before and after washout with saline (log 9.7-log 9.7 organisms/ml) and saline had no influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…As with 90 mL of sodium phosphate, 34 senna can be considered the standard for elective colonic or rectal resection. Further progress can be expected when senna vs sodium phosphate, various combinations of oral and systemic antibiotics, and other antiseptic enemas (povidone vs hypochlorite) 36…”
Section: Resultsmentioning
confidence: 99%
“…As with 90 mL of sodium phosphate, 34 senna can be considered the standard for elective colonic or rectal resection. Further progress can be expected when senna vs sodium phosphate, various combinations of oral and systemic antibiotics, and other antiseptic enemas (povidone vs hypochlorite) 36…”
Section: Resultsmentioning
confidence: 99%
“…A recent review from the Mayo Clinic was sceptical about PVI usefulness in colon surgery, nevertheless the authors concluded that in the acute setting peritoneal or wound irrigation with PVI may be useful in dirty or contaminated operations [8]. It has been suggested that Sodium Hypochlorite is more active on E. coli than PVI [9], but its use should be avoided as it is associated with higher rate of complications [7-10]. However, also colonic irrigation with PVI has some local and systemic effects, as from an animal model: 30 minutes exposure to 5 percent PVI caused severe colonic mucosal injury, with detachment of the epithelial cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, the margin of safety also could be enhanced further by specific means of preoperative antibiotic bowel decontamination [13][14][15]. However, the main intellectual innovation in our technique lies in its obviation of the daunting requirement to close the transcolonic passageway to the pelvis because the fecal flora, combined with the thin wall of the viscus, affords zero tolerance of any flaw in a prospective seal.…”
Section: Discussionmentioning
confidence: 99%